Dengue Hemorrhagic Fever in Jepara Indonesia: Reporting Data From The Discrict Disease Surveillance - Wijayanti, Nani Dwi; Ilmi, Laili Rahmatul; Nisak, Umi Khoirun; Widayati, Eka; Pramesti, Febryan Nidya; Ningsih, Eka Rahma (Procedia of Engineering and Life Science, 2024)
Indonesia is a tropical country vulnerable to infectious diseases, including dengue fever caused by mosquito bites. Dengue fever cases are a burden on the world because they can cause death. WHO reported that in May 2024, there were a total of 465 cases in districts/cities in 34 provinces, the national death rate until May 2024 was 777 deaths. Recording a complete medical record can support good disease reporting. This study aims to determine the distribution of dengue fever cases in Jepara district, Central Java in 2023-2024. The method of this study is descriptive. The population is disease reports in 2023 and 2024, and the sample used is the dengue fever disease report for the period January - May 2024 with random sampling techniques. Data imported from Microsoft Access is processed with a stata application and narrated descriptivelyThe number of dengue fever sufferers spread across 16 sub-districts is 3,549 with 1,728 male and 1,821 female sufferers. Of the 16 sub-districts, the highest number is in Pecangaan District 543 cases, and the lowest cases are in Karimunjawa District. The category of patients based on the highest age group in category 1 (0-4 years old) was 2,136 (60.17%), with the highest mortality rate in category 2 (5-14 years old) as many as 12 people and the highest CFR at Kartini Hospital with a total of 19%, namely 12.9% in male patients and 7.24% in female patients. (dengue fever, cases, reporting). Dengue fever, Jepara District, Case Fatality Rate, Age group, Epidemiology